2020
DOI: 10.3892/ol.2020.11601
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in MEN1 are associated with the tumorigenesis of pituitary adenoma associated with meningioma

Abstract: Pituitary adenoma and meningioma are two of the most common benign tumors in the central nervous system. Pituitary adenoma associated with meningioma (PAM) is a rare disease, the tumorigenesis of which remains unclear. Therefore, the aim of the present study was to investigate the tumorigenesis of PAM. A total of 8,197 patients with pituitary adenoma were analyzed. Furthermore, the clinical data of 57 patients with PAM were compared with patients with multiple endocrine neoplasia 1 (MEN-1) syndrome. Whole exom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…In our series, three adenomas were over-secreting at the time of progression in Hardy's classification, suggesting that tumour progression could have been diagnosed by monitoring hormonal secretion followed by MRI, even in the absence of systematic MRI follow-up. Conversely, the presence of a meningioma (the prevalence of which is higher in MEN1 patients (18,19)) will necessarily influence the monitoring rate of subsequent brain and pituitary imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, three adenomas were over-secreting at the time of progression in Hardy's classification, suggesting that tumour progression could have been diagnosed by monitoring hormonal secretion followed by MRI, even in the absence of systematic MRI follow-up. Conversely, the presence of a meningioma (the prevalence of which is higher in MEN1 patients (18,19)) will necessarily influence the monitoring rate of subsequent brain and pituitary imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of pituitary adenoma, younger age, and larger size of meningioma have been shown to be significantly associated with MEN1 mutation. 16 …”
Section: Discussionmentioning
confidence: 99%
“…International Journal of General Medicine 2020:13 1246 pituitary adenoma, younger age, and larger size of meningioma have been shown to be significantly associated with MEN1 mutation. 16 Mathuriya et al 17 suggested that hormones may contribute to the occurrence of meningiomas.…”
Section: Dovepressmentioning
confidence: 99%
“…Thus far there has been no strong evidence supporting a role of MEN1 in the pathogenesis of meningiomas ( 118 ). Zhu and colleagues recently studied tumors from patients diagnosed with both pituitary adenoma and meningioma (PAM) ( 119 , 120 ). In their first study of 57 PAM patients, tumors from PAM patients, compared with “sporadic” pituitary adenomas or meningiomas, had lower MEN1 expression and, in turn, hyperactivation of the mTOR signaling pathway ( 119 ).…”
Section: Central Nervous System Tumorsmentioning
confidence: 99%
“…In their first study of 57 PAM patients, tumors from PAM patients, compared with “sporadic” pituitary adenomas or meningiomas, had lower MEN1 expression and, in turn, hyperactivation of the mTOR signaling pathway ( 119 ). A follow up study reported that 5/23 patients with PAM harbored a germline missense MEN1 variant (c.1523G>A; p.G508D), but none of those patients had other MEN1 clinical manifestations and thus did not have MEN1 ( 120 ). This variant is also considered benign or likely benign by ClinVar ( 121 ).…”
Section: Central Nervous System Tumorsmentioning
confidence: 99%